2007
DOI: 10.3114/sim.2007.58.08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis and pathogenicity of the Cladophialophora carrionii complex, with the description of a novel species

Abstract: Cladophialophora carrionii is one of the four major etiologic agents of human chromoblastomycosis in semi-arid climates. This species was studied using sequence data of the internal transcribed spacer region of rDNA, the partial β-tubulin gene and an intron in the translation elongation factor 1-alpha gene, in addition to morphology. With all genes a clear bipartition was observed, which corresponded with minute differences in conidiophore morphology. A new species, C. yegresii, was introduced, which ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 44 publications
1
61
0
Order By: Relevance
“…These A. flavus strains were identified on the basis of macroscopic and microscopic morphological characteristics. The morphological identification of the Aspergillus flavus isolates was verified by internal transcribed spacer 1 (ITS1), 5.8S, and ITS2 region rRNA sequence analysis, as described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…These A. flavus strains were identified on the basis of macroscopic and microscopic morphological characteristics. The morphological identification of the Aspergillus flavus isolates was verified by internal transcribed spacer 1 (ITS1), 5.8S, and ITS2 region rRNA sequence analysis, as described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…The fungal "giant cell" is a central cell in dimorphism that enables rapid change between waterborne yeast and hydrophobic filamentous growth, and vice versa. Hydrophobic, catenate conidia (anamorph genus Cladophialophora) may serve for airborne dispersal (37). In the human host, hydrophobicity may explain the neurotropic character of some severe pathogens, such as Cladophialophora bantiana.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…A striking example is the species pair Cladophialophora carrionii and Cladophialophora yegresii, which are nearly exclusively found as agents of human disease and on cactus thorns, respectively (37).…”
Section: Pathogenicity and Virulencementioning
confidence: 99%
“…Cladophialophora carrionii and C. yegresii, however, tolerate higher temperatures (both species can grow at 37 °C; de Hoog et al 2007). Furthermore, a phialidic synasexual stage occasionally produced by C. carrionii (de Hoog et al 2000), was not observed in C. pseudocarrionii.…”
Section: Molecular and Morphological Studymentioning
confidence: 99%